A comparative biomechanical analysis of pretzel: A novel arthroscopic suture knot [Geliştirilen yeni artroskopik düǧüm pretzel'in karşilaştirmali biyomekanik analizi] - (:unkn) unknown (My University, 2009)
The purpose of this paper is to evaluate the biomechanical properties of a novel arthroscopic knot, Pretzel knot to be used in shoulder surgeries and compare it with two knots taken as standard: Samsung Medical Center(SMC) and Nicky's knots. Two groups have been formed: unbacked group (Pretzel and SMC knots), backed group (Pretzel, SMC and Nicky's knots backed with 3 RHAPs). Both groups have been tested with load to failure test and cyclic loading test. Parameters consideredfor both groups were for loop security, mechanism of failure, permanent loosening, load at failure and elongation at failure. There was significant improvement in loop security for Pretzel compared to SMC knot in unbacked case. Also elongation at failure in backed case is significantly lower for Pretzel compared to SMC whereas all other results were similar. Results showed that Pretzel knot may be safely used in arthroscopic surgeries and shows an improvement in loop security which gives an advantage in surgeries on pretensioned tissues. ©2009 IEEE.